Tiara[5]arenes: Synthesis, Solid‐State Conformational Studies, Host–Guest Properties, and Application as Nonporous Adaptive Crystals. (21st January 2020) - Yang, Weiwei; Samanta, Kushal; Wan, Xintong; Thikekar, Tushar Ulhas; Chao, Yang; Li, Shunshun; Du, Ke; Xu, Jun; Gao, Yan; Zuilhof, Han; Sue, Andrew C.‐H.
Abstract: Tiara[5]arenes (T[5]s), a new class of five‐fold symmetric oligophenolic macrocycles that are not accessible from the addition of formaldehyde to phenol, were synthesized for the first time. These pillar[5]arene‐derived structures display both unique conformational freedom, differing from that of pillararenes, with a rich blend of solid‐state conformations and excellent host–guest interactions in solution. Finally we show how this novel macrocyclic scaffold can be functionalized in a variety of ways and used as functional crystalline materials to distinguish uniquely between benzene and cyclohexane. Abstract : Ein kleines Krönchen : Tiara[5]arene, eine Klasse von fünffach symmetrischen Oligophenol‐Makrocyclen, die nicht durch direkte Phenol‐Formaldehyd‐Kondensation zugänglich sind, wurden mittels Umwandlung von Pillar[5]arenen synthetisiert.